1+4n=-13-7n-6-2

Simple and best practice solution for 1+4n=-13-7n-6-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+4n=-13-7n-6-2 equation:


Simplifying
1 + 4n = -13 + -7n + -6 + -2

Reorder the terms:
1 + 4n = -13 + -6 + -2 + -7n

Combine like terms: -13 + -6 = -19
1 + 4n = -19 + -2 + -7n

Combine like terms: -19 + -2 = -21
1 + 4n = -21 + -7n

Solving
1 + 4n = -21 + -7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '7n' to each side of the equation.
1 + 4n + 7n = -21 + -7n + 7n

Combine like terms: 4n + 7n = 11n
1 + 11n = -21 + -7n + 7n

Combine like terms: -7n + 7n = 0
1 + 11n = -21 + 0
1 + 11n = -21

Add '-1' to each side of the equation.
1 + -1 + 11n = -21 + -1

Combine like terms: 1 + -1 = 0
0 + 11n = -21 + -1
11n = -21 + -1

Combine like terms: -21 + -1 = -22
11n = -22

Divide each side by '11'.
n = -2

Simplifying
n = -2

See similar equations:

| -5g-(8+g)=12 | | (2x-3)+(3x-2)=90 | | x^2=4x+1 | | 2x-4x-11=-2x+9-11 | | 5c+6c-2c+4c= | | 15-b=7 | | 6(t-3)+6t=4(3t+3)-9 | | 2(z-3)-(-9z-5)=10 | | 10n^2-n-2=0 | | (2b)+b-12+b-12=21 | | .5h+.3h+-2=.83h+2 | | 2C+30=59 | | -5+(8+g)=12 | | 1/2(6x+5)=x+2(x+1) | | b-2+8b=30 | | -2p-3(p-8)=31-5p | | (3x^3+6x^2-x+8)(5x-9)= | | 3X+5y+15=0 | | 2x+5(-3x+3)=-50 | | 9a+7a=4 | | 15=7x+3-3x | | -3x+=4x+9-7x | | 2n=.11 | | 75x+200=950 | | -8-2x=-8(1+8x) | | 8k=.4 | | 2x+3y=79.72 | | -9+11x=211 | | 7k+1=6(2k+6) | | (.1666666667)-.7777777778x=x+1.5x | | x+5y-x+11y= | | -5+k/14=-1 |

Equations solver categories